How things work : discover secrets and science behind medieval machines, jet packs, movie magic, and everything in between - Resler, Tamara J. (Washington, D.C. : National Geographic, 2018)
Look inside, take it apart, turn it over, and figure out how things work! Quippy descriptions, full-color diagrams, and brilliant photographs make even the most intimidating subjects completely accessible--and totally fun! (We're looking at you, space robots.) For every explanation, we touch on basic principles and then dive deeper. Just want to know what terraforming is? We've got you covered. Want to know how to terraform, say, Mars? We'll explain that, too. But this book isn't just for explaining things. We'll also introduce you to the dreamers, scientists, and innovators who create this amazing stuff. You'll meet a NASA engineer, an underwater archaeologist, and a chocolate scientist. You'll learn what it's like to fly a plane into the eye of a hurricane--on purpose. -- from Amazon.
Blast from the past -- Out of this world -- Our crazy planet -- I scream, you scream -- Lights, camera... action!
OSLIS\Gale Nat Geo eBooks(2/2/23).
At head of title: National Geographic Kids.
Includes bibliographical references (pages 200-201) and index.
Age: 8-12.
Grade 4 to 6.
Description based on print version record.
Keywords: Machinery -- History -- Juvenile literature; Inventions -- History -- Juvenile literature; Technology -- History -- Juvenile literature; Machinery -- History; Inventions -- History; Technology -- History; JUVENILE NONFICTION -- Technology -- General; Inventions; Machinery; Technology; Electronic books- OSLIS; Trivia and miscellanea; Illustrated works; History; Juvenile works; Trivia and miscellanea; Illustrated works; Electronic books